Optical surface modes in a system of fine metallic particles - Blank, A. Ya.; Garanina, L. V.; Grechko, L. G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The interaction of electromagnetic radiation with a low-density disordered system of fine metallic particles located in a dielectric matrix is considered in a quasi-static approach with allowance for dipole-dipole interaction. The electric dipole moment of the system is calculated in a pair approximation. The case of nonidentical particles differing in their sizes or dielectric functions is presented. Allowance for particle nonidentity leads to doubling of the number of their surface modes and to the appearance of band gaps in the spectrum. The spectrum peculiarities are revealed in the fine structure of electromagnetic absorption.